2021
DOI: 10.3390/healthcare9040382
|View full text |Cite
|
Sign up to set email alerts
|

Woman’s Needs and Satisfaction Regarding the Communication with Doctors and Midwives during Labour, Delivery and Early Postpartum

Abstract: The study aimed to identify the difference in communication needs of women giving birth and women during early postpartum. An additional goal includes the analysis of the experience and communication needs through the context of a woman’s approach to childbirth. The study is a cross-sectional, self-report survey; 521 women between 5 and 10 days after birth participated in the study. Women perceived information provided by the medical staff as the most helpful aspect of verbal communication both during labour a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Firstly, education empowers mothers and their husbands, granting them greater autonomy to access healthcare services and advocate for their rights [31]. Additionally, they may possess better communication skills and assertiveness to claim their rights and preferences during childbirth, thereby reducing the likelihood of experiencing D&A [32]. Furthermore, higher education often leads to improved socio-economic status, re ected in higher wealth quintiles, which provide mothers with affordability to access private healthcare facilities where the quality of care and treatment may be higher, thereby reducing the risk of experiencing D&A compared to public facilities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, education empowers mothers and their husbands, granting them greater autonomy to access healthcare services and advocate for their rights [31]. Additionally, they may possess better communication skills and assertiveness to claim their rights and preferences during childbirth, thereby reducing the likelihood of experiencing D&A [32]. Furthermore, higher education often leads to improved socio-economic status, re ected in higher wealth quintiles, which provide mothers with affordability to access private healthcare facilities where the quality of care and treatment may be higher, thereby reducing the risk of experiencing D&A compared to public facilities [33].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the previous systematical review of physician-patient communication in primary care offices [ 46 ] also found that physicians verbal and nonverbal behavior can increase patient satisfaction. In addition, in the study of maternal needs, it was found that verbal and non-verbal physician communication was beneficial with regards to ensuring a healthy delivery [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Baranowska et al (2021) illustrated that midwives' communication skills in creating childbirth satisfaction with labor and delivery are important. In addition, verbal and nonverbal communication is one of the effective issues in maternal satisfaction during childbirth [30]. The findings of other studies emphasized that communication-based training programs result in the empathy and sympathy between care providers and women during childbirth and assist in enhancing childbirth satisfaction [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%